A real options approach to amenity valuation: The role of uncertainty and risk aversion. (10th August 2017) - Mense, Andreas
Abstract: Many empirical studies in the fields of urban and environmental economics rely on the hedonic pricing framework. This paper draws attention to two important elements that are not covered by this theory: uncertainty and relocation costs. It develops a theoretical model where agents face uncertainty, but may accumulate savings as a form of self‐insurance. It shows that uncertainty pushes up relocation costs due to the option value of waiting, while self‐insurance helps to reduce this lock‐in problem. Moreover, the model suggests that the implicit price of environmental quality increases with uncertainty even if agents are risk‐neutral.